Direct Z-Scheme charge transfer in heterostructured MoO3/g-C3N4 photocatalysts and the generation of active radicals in photocatalytic dye degradations. (July 2019) - Xue, Shengyang; Wu, Chunzheng; Pu, Shengyan; Hou, Yaqi; Tong, Tian; Yang, Guang; Qin, Zhaojun; Wang, Zhiming; Bao, Jiming
Abstract: Photocatalytic degradation is an attractive strategy to purify waste water contaminated by macromolecular organics. Compared with the single-component photocatalysts, heterostructures of different semiconductors have been widely used to improve the photocatalytic performance. In this work, we fabricate a hetero-structured photocatalyst consisting of two-dimensional graphitic carbon nitride (g-C3 N4 ) nanosheets and commercial MoO3 microparticles through a simple mixing and annealing process. The photocatalytic performance was evaluated in various dye degradation reactions, especially Rhodamine (RhB) degradation. The MoO3 /g-C3 N4 composite shown a significant improvement compared with individual MoO3 or g-C3 N4 as well as their physical mixture. By applying electron spin resonance (ESR) spin-trap spectra, radical scavenge experiments and electrochemical analysis, we find that a direct Z-scheme charge transfer between MoO3 and g-C3 N4 not only causes an accumulation of electrons in g-C3 N4 and holes in MoO3, but also boosts the formation of superoxide radical and hydroxyl radical. The superoxide radical and hole dominate the photocatalytic degradation, while the hydroxyl radical plays a negligible role and its production can be suppressed by lowering the pH value. Graphical abstract: Image 1 Highlights: A simple mixing – annealing method was used to prepare MoO3 /g-C3 N4 heterostructures. The strong interaction between the two components resulted in a synergy in photocatalytic dye degradations. A Z-Scheme charge transfer between the two components was proved. Hole and ·O2 − play vital roles in the degradation of RhB, while the produced ·OH radicals are not active. The conversion of holes to ·OH can be suppressed by lowering the pH value.